Innate Immune Responses in ALV-J Infected Chicks and Chickens with Hemangioma In Vivo - Feng, Min; Dai, Manman; Xie, Tingting; Li, Zhenhui; Shi, Meiqing; Zhang, Xiquan (Frontiers in Microbiology, 2016)
Avian leukosis virus subgroup J (ALV-J) infection can cause tumors and immunosuppression. Since the precise mechanism of the innate immune response induced by ALV-J is unknown, we investigated the antiviral innate immune responses induced by ALV-J in chicks and chickens that had developed tumors. Spleen levels of interleukin-6 (IL-6), IL-10, IL-1β and interferon-β (IFN-β) were not significantly different between the infected chick groups and the control groups from 1 day post hatch to 7 days post hatch. However, IL-6, IL-1β and IFN-β protein levels in the three clinical samples with hemangiomas were dramatically increased compared to the healthy samples. In addition, the anti-inflammatory cytokine IL-10 increased sharply in two of three clinical samples. We also found a more than 20-fold up-regulation of ISG12-1 mRNA at 1 day post infection (d.p.i.) and a 2-fold up-regulation of ZC3HAV1 mRNA at 4 d.p.i. However, there were no statistical differences in ISG12-1 and ZC3HAV1 mRNA expression levels in the tumorigenesis phase. ALV-J infection induced a significant increase of Toll-like receptor 7 (TLR-7) at 1 d.p.i. and dramatically increased the mRNA levels of melanoma differentiation-associated gene 5 (MDA5) in the tumorigenesis phase. Moreover, the protein levels of interferon regulatory factor 1 (IRF-1) and signal transducer and activator of transcription 1 (STAT1) were decreased in chickens with tumors. These results suggest that ALV-J was primarily recognized by chicken TLR7 and MDA5 at early and late in vivo infection stages, respectively. ALV-J strain SCAU-HN06 did not induce any significant antiviral innate immune response in one week old chicks. However, interferon-stimulated genes were not induced normally during the late phase of ALV-J infection due to a reduction of IRF1 and STAT1 expression.